2018
DOI: 10.3928/00220124-20180116-09
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Review of Interprofessional Simulation in Nursing Practice

Abstract: Structured simulation research designs using published guidelines for best practice implementation are needed. J Contin Educ Nurs. 2018;49(2):91-96.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Results of this review suggests there remains a hierarchy in today's society, with the reluctance of nurses to escalate to more senior members. There is a strong body of evidence emerging which highlights the effectiveness of simulation as a teaching method among nurses and doctors to improve practice and working relationships (Aggarwal et al, 2010;Goolsarran, Hamo, Lane, Frawley, & Lu, 2018;O'Rourke, Horsley, Doolen, Mariani, & Pariseault, 2018;Stayt, Merriman, Ricketts, Morton, & Simpson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Results of this review suggests there remains a hierarchy in today's society, with the reluctance of nurses to escalate to more senior members. There is a strong body of evidence emerging which highlights the effectiveness of simulation as a teaching method among nurses and doctors to improve practice and working relationships (Aggarwal et al, 2010;Goolsarran, Hamo, Lane, Frawley, & Lu, 2018;O'Rourke, Horsley, Doolen, Mariani, & Pariseault, 2018;Stayt, Merriman, Ricketts, Morton, & Simpson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the abilities of the study group were higher than those of the control (p < 0.05), which indicated that in surgical nursing practice teaching, cross-professional education and situational simulation teaching were more conducive to improving students' abilities. Cross-professional education and situational simulation teaching play an important role in nursing teaching, and the application of this method in clinical nursing teaching can enable students to master more medical knowledge on the basis of the original, improve students' knowledge in a wide range of aspects, and deepen their knowledge of nursing (Jennifer et al, 2018). Next, the operation in the operating room requires the good cooperation of medical staff, and the effective integration of this method into nursing teaching can significantly improve the cooperation degree and cooperation ability of medical staff.…”
Section: Cross-professional Education and Situational Simulation Teaching Can Improve Students' Abilitiesmentioning
confidence: 99%
“…The use of blinded external assessors constitutes the main strength of this study; most studies report on students' or health professionals' self-reported learning experiences, 22 23 and studies have compared self-reporting and objective measurements without finding any correlation between these. 24 25 The major weaknesses were the number of teams, the relatively low number of observations for each team, the absence of a control group and the lack of prior validation of the questions that formed the basis of the assessments.…”
Section: Strengths and Limitationsmentioning
confidence: 99%